Morfologia das cipselas de Disynaphiinae e Praxelinae (Eupatorieae - Asteraceae) - Silva, Taynara Dayane Guimarães (2016)
Asteraceae (=Compositae) is one of the largest families of plants, comprises about 1,600 genera and 23,000 species. The family has a wide distribution in Brazil occurring in different vegetation formations. The Disynaphiinae and Praxelinae subtribes belong to Eupatorieae tribe, which currently has 19 subtribes. The cypselae and its accessory parts (pappus and carpopodium) have great taxonomic value and can be used as diagnostic to differentiate or group species and even genera. The boundaries between some genera are not well defined based on morphological usual features. The study of the morphology of cypselae in Disynaphiinae and Praxelinae will contribute to the characterization and can understanding their infrageneric relations. The aim is to describe the structure of the pericarp of the mature fruit of the representatives of Disynaphiinae and Praxelinae as well as the varieties of Chromolaena squalida, seeking common morphological characteristics distinct to these groups. Thereunto, we used a scanning electron microscopy and light microscopy. The trichomes, pericarp structure, and accessory parts of cypselae proved useful in taxonomic groups revealing a close relationship between species of each of the subtribes. These features were also important to exclude species e. g. Disynaphia praeficta. Our study also supports the varieties of Chromolaena squalida, allowing the correct identification. The phytomelanin was present in all cypselae studied, but their arrangement differs among the subtribes. The correlation between the number of bundles and ribs is not fixed in Praxelinae and ribs were not always associated with vascular bundles.